EFFECT OF CLOSED AQUACULTURE SYSTEM APPLICATIONS OF RECIRCULATING AQUACULTURE SYSTEM AND RECIRCULATING AQUACULTURE SYSTEM-ZERO WATER DISCHARGE HYBRID SYSTEM ALONG WITH SYNBIOTIC FEED SUPPLEMENTATION ON WATER QUALITY, GROWTH PERFORMANCE, AND NUTRITIONAL PROFILE OF TILAPIA (OREOCHROMIS NILOTICUS) - Nur Fadillah, Anggie
Tilapia (Oreochromis niloticus) is one of the main commodities of freshwater fish in Indonesia. Tilapia aquaculture has not shown optimal performance so that the development is carried out with the closed aquaculture system applications such as Recirculation Aquaculture System / RAS and Recirculating Aquaculture System-Zero Water Discharge / RAS-ZWD hybrid system along with functional feed application with synbiotic supplementation. This study aims to determine the effect of the application of RAS and RAS-ZWD hybrid systems, as well as RAS with and without synbiotic feed supplementation on growth performance, water quality, and nutritional profile of tilapia. The study began with the preparation and conditioning system of RAS, RAS-ZWD hybrid, and production of symbiotic feed using a prebiotic content of 108 CFU / kg feed and 0,5% of Spirulina platensis microalgae. Furthermore, tilapia rearing was carried out for 60 days of culture period which consisted of two test stages: (1) comparison between RAS-ZWD hybrid system (‘RH’) and RAS system (control/’K’) both of which were given commercial feed, and (2) comparison between RAS with synbiotic feed supplementation (‘RS’) and RAS with commercial feed (control/’K’). Analysis of water quality parameters, biological parameters, and fish proximate was carried out after 60 days of culture period. The result showed that water quality parameters such as temperature, Dissolved Oxygen (DO), pH, ammonium, nitrite, and nitrate in RH, K, and RS treatments were below the tolerance limit for the growth of tilapia, and K had the best water quality parameters. Growth performance in K treatment such as Average Daily Growth (ADG) (1,081 ± 0,138 gr/day), Specific Growth Rate (SGR) (7,317 ± 0,002 %), Feed Conversion Ratio (FCR) (1,149 ± 0,054), survival (82,667 ± 0,070 %), final biomass (1,680 ± 0,078 kg) and productivity (16,802 ± 0,783 kg/m3) were higher and significantly different from the RH treatment (P<0,05). After improvement with synbiotic feed, RS treatment had higher growth performance such as ADG (1,235 ± 0,113 gr/day), SGR (7,560 ± 0,002 %), FCR (1,043 ± 0,046), survival (80,000 ± 0,141 %), final biomass (1,743 ± 0,127 kg) and productivity (17,427 ± 1,270 kg/m3), but not significantly different from treatment K (P>0,05). There was a correlation between length and weight of fish in three treatments, with a negative allometric growth pattern (b<3) for RH and K and a positive allometric growth pattern (b>3) in RS. The relative condition factor in the three treatments was close to 1 indicating a good health condition of the fish. Furthermore, the nutritional profile of three treatments was in the optimum range, protein and ash content in RH treatment were higher and significantly different from K treatment (P<0,05). However, improvement with synbiotic feed (RS) could not improve nutritional profile except carbohydrate and water content. It can be concluded that RAS system can significantly improve the growth performance of tilapia compared to RAS-ZWD hybrid system with good water quality parameters and nutritional profile. Meanwhile, RAS system with synbiotic feed supplementation is able to support the growth performance of tilapia with sufficiently maintained water quality parameters, but it has not been able to improve the nutritional profile except carbohydrate and water content.